Neural Dynamics of Processing Probability Weight and Monetary Magnitude in the Evaluation of a Risky Reward - Wang, Guangrong; Li, Jianbiao; Wang, Pengcheng; Zhu, Chengkang; Pan, Jingjing; Li, Shuaiqi (Frontiers in Psychology, 2019)
Risky decision making involves risky reward valuation, choice, and feedback processes. However, the temporal dynamics of risky reward processing are not well understood. Using event-related brain potential, we investigated the neural correlates of probability weight and money magnitude in the evaluation of a risky reward. In this study, each risky choice consisted of two risky options, which were presented serially to separate decision-making and option evaluation processes. The early P200 component reflected the process of probability weight, not money magnitude. The medial frontal negativity (MFN) reflected both probability weight and money magnitude processes. The late positive potential (LPP) only reflected the process of probability weight. These results demonstrate distinct temporal dynamics for probability weight and money magnitude processes when evaluating a risky outcome, providing a better understanding of the possible mechanism underlying risky reward processing.